Code is speech: legal tinkering, expertise, and protest among free and open source software developers. - Coleman, Gabriella (Cultural Anthropology, 2009)
In this essay, I examine the channels through which Free and Open Source Software (F/OSS) developers reconfigure central tenets of the liberal tradition—and the meanings of both freedom and speech—to defend against efforts to constrain their productive autonomy. I demonstrate how F/OSS developers contest and specify the meaning of liberal freedom—especially free speech—through the development of legal tools and discourses within the context of the F/OSS project. I highlight how developers concurrently tinker with technology and the law using similar skills, which transform and consolidate ethical precepts among developers. I contrast this legal pedagogy with more extraordinary legal battles over intellectual property, speech, and software. I concentrate on the arrests of two programmers, Jon Johansen and Dmitry Sklyarov, and on the protests they provoked, which unfolded between 1999 and 2003. These events are analytically significant because they dramatized and thus made visible tacit social processes. They publicized the challenge that F/OSS represents to the dominant regime of intellectual property (and clarified the democratic stakes involved) and also stabilized a rival liberal legal regime intimately connecting source code to speech. Reprinted by permission of the publisher.